Efficiency of application of different apple trees protection systems against harmful organisms in the Precarpathian province of the Carpathian mountain area of Ukraine - Hunchak, M.; Zaitsev, Yu.; Shapran , S. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2023)
Goal. Study of the efficiency of application of chemical, biological and biological-chemical protection systems of apple trees against harmful organisms in the conditions of the Precarpathian province of the Carpathian mountain zone of Ukraine. Methods. Phytosanitary monitoring was carried out visually and with the help of pheromone traps. Phytophagous colonization and disease development were recorded according to generally accepted methods in the phases of apple development: «swelling of buds», «green cone», «bud extension», «bud separation», «pink bud», «blooming», «end of flowering», «fruit formation», «fruit growth» and «fruit ripening». The technical effectiveness of insecticides was determined after 5 and 7 days, and the effectiveness of fungicides — after 7 days. Statistical processing of research results was carried out by the method of variance analysis. Results. The results of monitoring the phytosanitary state of apple plantations established that the most common pests in 2018—2020 in the conditions of the Precarpathian Province of the Carpathian Mountain Zone of Ukraine were: apple fruit borer (37.2%), aphids (19.5%), leafhoppers (12.2%), mites (8.0%), apple moth (8.3%), flower eater (7.9%), hairy deer (6.9%); the most common diseases: scab (38.2%), powdery mildew (32.8%), moniliosis (14.2%), fruit rot (14.8%). All studied apple tree protection systems against harmful organisms in the conditions of the Precarpathian province of the Carpathian mountain zone of Ukraine obtained high yield rates, and all protection systems allowed to reliably protect apple orchards from pests and diseases. The technical efficiency of the chemical protection system, which included 12 treatments with chemical pesticides, averaged 82.5—96.5%. Productivity using this system was 26.5—26.7 t/ha. The biological protection system, which was based on 7 treatments with biological preparations, made it possible to obtain an apple yield 22.4—22.9 t/ha. The technical efficiency of the preparations of the biological defense system was at the level 66.1% — 72.3%. The system of biological and chemical protection of apple trees against harmful organisms included 7 treatments, reducing the use of chemical protection agents to one treatment, which made it possible to significantly reduce the amount of chemical agents used, minimize the negative impact of pesticides on the ecosystem of the apple orchard, and obtain productivity 23.5—25.1 t/ ha, for the effectiveness of drugs 66.3 94.3%. Conclusions. When apple orchards are heavily colonized by pests and diseases, it is recommended to use a chemical protection system that includes 12 treatments with chemical pesticides (9 treatments with a mixture of insecticides and fungicides, 2 treatments with fungicides and one treatment with insecticides) in accordance with the 12 main phases of apple tree development in which the most harmful organisms inhabit and damage the ecosystem of the apple orchard during the period from the «green cone» phenophase to the «fruit ripening» phenophase. To reduce the use of chemical protection agents in apple orchards, a biological and chemical system should be used: in the «green cone» phenophase, one treatment with chemical pesticides, and in the «end of flowering» phenophase — «fruit ripening» — with biological preparations. Under the condition of complete withdrawal from the use of chemical pesticides, the system of biological protection of the apple tree should be used, which is based on seven treatments with biological preparations in the phenophase «separation of buds» — «ripening of fruits».